2015
DOI: 10.1002/ijc.29806
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine insecticides DDT and chlordane in relation to survival following breast cancer

Abstract: Organochlorine insecticides have been studied extensively in relation to breast cancer incidence and results from two meta-analyses have been null for late-life residues, possibly due to measurement error. Whether these compounds influence survival remains to be fully explored. We examined associations between organochlorine insecticides (p,p’-DDT, its primary metabolite, p,p’-DDE, and chlordane) assessed shortly after diagnosis and survival among women with breast cancer. A population-based sample of women di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 50 publications
2
24
0
4
Order By: Relevance
“…However, a recent study of 633 women diagnosed with invasive or in situ breast cancer found that organochlorines may adversely impact survival. The highest tertile of lipid‐adjusted p,p′ ‐DDT concentration in serum, but not p,p′ ‐DDE concentration, was associated with all‐cause (hazard ratio, 2.19; 95% CI, 1.02–4.67) and breast cancer‐specific (hazard ratio, 2.72; 95% CI, 1.04–7.13) mortality at five years after diagnosis, supporting the adverse health effects of pesticide exposure …”
Section: Introductionmentioning
confidence: 83%
“…However, a recent study of 633 women diagnosed with invasive or in situ breast cancer found that organochlorines may adversely impact survival. The highest tertile of lipid‐adjusted p,p′ ‐DDT concentration in serum, but not p,p′ ‐DDE concentration, was associated with all‐cause (hazard ratio, 2.19; 95% CI, 1.02–4.67) and breast cancer‐specific (hazard ratio, 2.72; 95% CI, 1.04–7.13) mortality at five years after diagnosis, supporting the adverse health effects of pesticide exposure …”
Section: Introductionmentioning
confidence: 83%
“…On subsequent poor healing, scarring and contracture formation occurs on skin [13]. Organochlorines may also have carcinogenic effects [14][15][16][17][18][19][20]. Respiratory depressions may also occur.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the LIBCSP follow‐up design and ascertainment of vital status have also been previously reported . In brief, the National Death Index (NDI), a centralized database of death record information maintained by the National Center for Health Statistics, was used to ascertain date and cause of death for the women with BC.…”
Section: Methodsmentioning
confidence: 99%